2020
DOI: 10.4067/s0718-221x2020005000107
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical behavior of dowel connection for timber-concrete composite rural bridges

Abstract: This study focuses on the evaluation of the mechanical behavior of two types of connections for intended use in rural Timber-Concrete Composite traffic bridges. The two connection types used were the "X" type connection -XD and the dowel type connection -PD. Firstly, static shear tests in small-scale specimens were performed in both connection types and higher results were obtained for the XD series, both for stiffness and load carrying capacity. Secondly, the PD connection was chosen, based on practical and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Other researches on the same topic confirms it. Silva Marques et al (2020) it was concluded that the increase of load level in the cyclic tests affected the performance of the connection, leading to a decrease in stiffness. Although mechanical connectors such as coach screws, nails, dowels, etc.…”
Section: Composites With Continuously Distributed Connectorsmentioning
confidence: 99%
“…Other researches on the same topic confirms it. Silva Marques et al (2020) it was concluded that the increase of load level in the cyclic tests affected the performance of the connection, leading to a decrease in stiffness. Although mechanical connectors such as coach screws, nails, dowels, etc.…”
Section: Composites With Continuously Distributed Connectorsmentioning
confidence: 99%